1996
DOI: 10.1021/bi961951l
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Analog Study of the Role of Steric Interactions in the Excited State Isomerization Dynamics of Rhodopsin

Abstract: The role of intramolecular steric interactions in the isomerization of the 11-cis-retinal chromophore in the photoreceptor protein rhodopsin is examined with resonance Raman and CD spectroscopy combined with quantum yield experiments. The resonance Raman spectra and CD spectra of 13-demethylrhodopsin indicate that its chromophore, an analog in which the nonbonded interaction between the 10-H and the 13-CH3 groups is removed, is less distorted in the C10...C13 region than the native chromophore. The reduced tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(177 citation statements)
references
References 48 publications
14
159
1
3
Order By: Relevance
“…This approach is analogous to solution NMR, where residual dipolar couplings are used with distance restraints from nuclear Overhauser effect (NOE) spectroscopy. A highly distorted structure is found for retinal in the dark state, consistent with vibrational 9,[30][31][32] and circular dichroism (CD) spectroscopy 30,31 , and with bioorganic studies of rhodopsin 33,34 . Despite constraints of the binding cavity the ligand undergoes restricted motion, as shown by the rapidly spinning methyl groups, with significant off-axial fluctuations.…”
Section: Introductionsupporting
confidence: 67%
“…This approach is analogous to solution NMR, where residual dipolar couplings are used with distance restraints from nuclear Overhauser effect (NOE) spectroscopy. A highly distorted structure is found for retinal in the dark state, consistent with vibrational 9,[30][31][32] and circular dichroism (CD) spectroscopy 30,31 , and with bioorganic studies of rhodopsin 33,34 . Despite constraints of the binding cavity the ligand undergoes restricted motion, as shown by the rapidly spinning methyl groups, with significant off-axial fluctuations.…”
Section: Introductionsupporting
confidence: 67%
“…It has been shown that although the protein binding cavity is flexible to accommodate structurally modified retinals, it frequently leads to less efficient photoactivation and/ or less stable pigments in the ground state (21,39). This is also supported by the present finding that the stability and quantum efficiencies of 14-Me-Rh and 13-EtRh are lower than those of rhodopsin; the light-dependent PDE activity of 14-MeRh is also smaller.…”
Section: Discussionsupporting
confidence: 70%
“…Despite that three methyl environments are found for the retinal ligand in the dark state, upon 11-cis to trans isomerization ≈ two methyl sites are evident. Such a loss of retinal strain is consistent with two major planes of unsaturation following light absorption (1,34,(38)(39)(40). Application of transition state theory then allows us to connect the T 1Z results with the energetic parameters for retinal bound to rhodopsin (Table 1).…”
Section: Generalized Model-free Analysis Explains Retinal Structure Andmentioning
confidence: 56%